THE EFFECTIVENESS OF CRIMINAL LAW ENFORCEMENT ON PROHIBITED DRUG LIST G ABUSE IN THE PERSPECTIVE OF LEGAL CERTAINTY - Masyur Mansyur; Wiryanto Wiryanto; Syarif Fadillah (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2023)
Research on the Effectiveness of Criminal Law Enforcement Against Abuse of Illegal Drugs List G in the Perspective of Legal Certainty. This study aims to analyze how law enforcement against drug abuse of list G according to criminal law; to analyze the law enforcement policy on drug abuse of list G in the future. The research methods used in obtaining the data or materials in the study include: normative legal research. This research uses a statutory approach. This research is descriptive analytical and literature. The data analysis technique used is that all primary, secondary and tertiary legal materials are collected, then the legal material is processed qualitatively with a statute approach, namely reviewing legislation to answer legal issues that have been formulated. The results of this study are law enforcement against perpetrators who abuse List G drugs by consuming wrongly so that they become addicts to List G drugs can be charged with Articles 197 and 198 of the Health Law with a maximum penalty of 15 years and a maximum fine of Rp. 1,500,000,000 (one billion five hundred million rupiah) for people who abuse it, whether it's producing, distributing, and selling list G drugs without a doctor's prescription. In addition, the perpetrators of drug abuse on list G can also be charged with Article 114 Paragraph (2) of Law Number 35 of 2009 concerning Narcotics which states that: that any person without rights or against the law owns, keeps, controls or provides narcotics class I non-plants, shall be punished with imprisonment for a minimum of 4 (four) years and a maximum of 12 (twelve) years and a minimum fine of Rp 800,000,000 , - (eight hundred million rupiah) and a maximum of Rp 8,000,000,000 (eight billion rupiah); and future criminal law policies against drug abusers of List G are given through PERMENKES No 7/2018 which classifies one of the list G drugs that is often misused, namely Karisoprodol as Narcotics Category I. In other words, law enforcement against abusers of Karisoprodol uses Law 35/2009. For producers and dealers there are sanctions in accordance with the provisions in Law 35/2009 and for Karisoprodol addicts have the same rights as narcotics users, namely to get the right to rehabilitation, but the agency states that Permekes 7/2018 cannot be applied because of inadequate facilities and infrastructure to carry out law enforcement.